2008
DOI: 10.1016/j.jss.2007.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Ischemia-Reperfusion Injury Alters Purinergic Receptor Expression in Clinically Relevant Extraintestinal Organs

Abstract: Background-Intestinal ischemia-reperfusion (IIR) injury is known to initiate the systemic inflammatory response syndrome which often progresses to multiple organ failure. We investigated changes in purinoceptor expression in clinically relevant extra-intestinal organs following IIR injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
(85 reference statements)
1
17
1
3
Order By: Relevance
“…Ischemia-reperfusion of the rat intestine causes a decrease in the expression of P2X 2 receptors on neurons of the myenteric and submucosal plexuses, as well as a decrease in density and of neurons immunoreactive for the P2X 2 receptor (Paulino et al, 2011). After intestinal ischemia-reperfusion injury, P2Y 2 receptor mRNA expression was increased in murine lung and kidney and A 3 receptor mRNA was increased in lung but decreased in kidney, but there was no change in mRNA expression of these receptors in the intestine (Milano et al, 2008). Protection from intestinal ischemia-reperfusion injury by hypoxiainducible factor-1a involves CD73 and A 2B receptors (Hart et al, 2011).…”
Section: Ischemiamentioning
confidence: 95%
“…Ischemia-reperfusion of the rat intestine causes a decrease in the expression of P2X 2 receptors on neurons of the myenteric and submucosal plexuses, as well as a decrease in density and of neurons immunoreactive for the P2X 2 receptor (Paulino et al, 2011). After intestinal ischemia-reperfusion injury, P2Y 2 receptor mRNA expression was increased in murine lung and kidney and A 3 receptor mRNA was increased in lung but decreased in kidney, but there was no change in mRNA expression of these receptors in the intestine (Milano et al, 2008). Protection from intestinal ischemia-reperfusion injury by hypoxiainducible factor-1a involves CD73 and A 2B receptors (Hart et al, 2011).…”
Section: Ischemiamentioning
confidence: 95%
“…It has been shown that the expression of P2X 7 , P2Y 2 , and P2Y 4 purinoceptor mRNAs is increased in the murine lung, kidney, and intestine following a 15-min occlusion of the superior mesenteric artery [31]. Changes in P2X 2 receptor expression, however, have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…IR causes intestinal dysfunction characterized by histological mucosa damage, decreased basal membrane integrity and impairment of barrier function 1 . The intestinal injuries triggered by ischemia also persist during reperfusion and involve activation of cytotoxic and inflammatory cascades and the expression or suppression of new gene products [1][2][3][4] . Although the molecular mechanisms underlying acute intestinal injury and repair after IR have not been completely elucidated, it is known that reactive oxygen species (ROS) play a role in acute intestinal injury after IR, in local tissue and in remote organs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanisms underlying acute intestinal injury and repair after IR have not been completely elucidated, it is known that reactive oxygen species (ROS) play a role in acute intestinal injury after IR, in local tissue and in remote organs. Therefore, intestinal IR promotes inflammation and multiorgan failure (MOF) [3][4][5][6] . Both, ROS and inflammatory cytokines play a role in kidney injury after IR intestinal 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation